Finite Element Modelling of Reinforced Concrete Beams Strengthened With FRP plates - JABBARI IZADI, AREZOO (IRC, 2015)
A finite element modelling of the reinforced concrete beams strengthened externally with fiber reinforced polymer (FRP) composites has been established using LS-DYNA program. A reinforced concrete beams were modelled in the software and the behaviour under static load was studied. In order to speed up the simulation, mass-scaling was also added. The value of mass-scaling was determined through trial and error. Afterwards, FRP plates were bonded to the beam and the static load was applied with a constant rate. The significant parameters that were investigated in this study were shear stress and the deflection of the beam. Furthermore, the values were compared to the experimental results to validate the simulation. As a result, a numerical method was proposed in which the effectiveness of utilizing FRP plates in concrete beams was investigated.